Phytoavailability of arsenic, cadmium, lead and mercury in rice grains of paddy plants grown in Malaysia - Che Fauziah I. (2022)
Agronomic practices in rice should follow best management practices (BMP) due to evidence of heavy metals accumulation in the grains either from agricultural inputs and/or soil. The practices such as application of fertilizer, soil amendments, pesticides and herbicides either under organic farming (OFS) or flooded conventional condition or system of rice intensification (SRI), have not been well investigated to reflect their impact in the rice grains. Among the trace elements that have become a concern in the rice grains are arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg). Recently, high levels of arsenic (As) in rice grain are reported in several literatures. Variability in total As, Cd, Pb and Hg in rice was evaluated using 12 rice samples from paddy growing areas of Malaysia. The data set is compared with the Maximum Permitted Concentration (MPC) as stated in the Malaysian Food Act (1983) and Food Regulation (1985) for reference values. The results were also evaluated based on previous background studies on heavy metals accumulation in rice grown in Malaysian soils which are from <1 to 2.59 mg kg⁻¹ for As, 0.004-0.04 mg kg⁻¹ for Cd, 0.10-0.70 mg kg⁻¹ for Pb and 0.05-6 µg kg⁻¹ for Hg. Trace metals accumulation in rice grains samples are found to be in the range of 0.03 to 12.90 mg kg⁻¹ for As, 0.011 to 0.612 mg kg⁻¹ for Cd, 0.09 to 3.33 mg kg⁻¹ for Pb and < 1 to 253.7 µg kg⁻¹ for Hg